The African francophone novel at the era of independences (1950-1960) : the construction of a new ethos of author - (:unkn) unknown (My University, 2017)
This research focuses on the identity that an author uniquely constructs and elaborates throughout his works. In doing so, the thesis reveals major discursive, argumentative and stylistic aspects of the literary works as well as of the image of their authors. Although their writing may be concerned with the future of their country, the artistic uniqueness of the work depends less on one’s African origins, and more on his connections to The World Republic of Letters as a member of the French literary field, taking into account the totality of literary and social discourses that constitute this field. This study wishes to examine the discursive Image (ethos) of two authors – Ousmane Sembène (Le docker noir 1956 et Les Bouts de bois de Dieu 1960) and Mongo Beti (Le Pauvre Christ de Bomba 1956 and Mission terminée 1957) – two of the most acclaimed “African writers” published before the time of the African Independence (1960’s).
Keywords: African Research